PROFILE OF PROSPECTIVE CHEMISTRY TEACHER IN DEVELOPING LEARNING TOOLS ACCORDING TO STANDARD PROCESS - Metridewi Primastuti; Regina Tutik padmaningrum (Pendidikan IPA, FMIPA, UNP, 2020)
In the educational unit, educator have to develop learning tools. In this study, learning tools are limited to the Lesson Plan (Rencana Pelaksanaan Pembelajaran/RPP). The lesson plan must be prepared in a complete and systematic structure according to the Standard Process. This research was conducted to analyze the profile ability of prospective chemistry teachers in developing lesson plan in accordance with the criteria of the RPP component in the Regulation of the Minister of Education and Culture of the Republic of Indonesia Number 22 of 2016 about Primary and Secondary Education Standard Process. This research method was descriptive with a quantitative approach. The research subject consisted of 10 chemistry education students in the 6th semester who were determined by purposive sampling. Research data was obtained through the RPP assessment rubric consisting of 8 indicators with a score of 1 to 4. The technique of data analysis is using percentage analysis, which are converted into the interval category criteria. Based on the analysis, it is known that profile of prospective chemistry teacher in developing lesson plans is in the good ability category.